Penerapan Wajib Militer di Indonesia - Ria Marsella; Putri Hilaliatu Badaria (SALAM: Jurnal Sosial dan Budaya Syar-i, 2015)
The legal basis for the implementation of this compulsory military service is stated in the Draft Reserved Component (Komcad) Law, where the Komcad is a military reserve force, consisting of civilians who have received basic military education, prepared to support the military as the main component during martial law. Military conscription rules first appeared in Law Number 29 of 1954 concerning the State Defense of the Republic of Indonesia. Furthermore, it is regulated separately which is thoroughly explained in Law Number 66 of 1958 concerning Military Compulsory Services. The problem that arises is that if military service continues, it will cause funding problems. Military conscription will of course require a large amount of funds in its implementation, while Indonesia's funding is still insufficient. This is evident in terms of funding for unfulfilled national defense priorities, such as the budget for overall defense and the main defense system tool (alutsista). In addition, the implementation of compulsory military service in Indonesia will threaten the constitutional rights of citizens as well as international covenants on human rights (HAM). Military conscription is considered contrary to or has the potential to violate several rights, especially the right to life, the right to freedom and security, freedom of thought, conscience and religion.Keywords: Military Conscription, International Covenant, National Defense Abstrak. Dasar hukum pelaksanaan wajib militer ini tertera dalam Rancangan Undang-Undang Komponen Cadangan (Komcad), yang mana Komcad adalah pasukan cadangan militer, terdiri dari warga sipil yang mendapat pendidikan militer dasar, dipersiapkan untuk mendukung militer sebagai komponen utama pada masa darurat perang. Aturan wamil pertama kali muncul dalam Undang-Undang Nomor 29 Tahun 1954 Tentang Pertahanan Negara Republik Indonesia. Selanjutnya diatur tersendiri yang secara menyeluruh dijelaskan dalam Undang-Undang Nomor 66 Tahun 1958 Tentang Wajib Militer. Permasalahan yang muncul adalah jika wajib militer ini tetap dilaksanakan yakni masalah pendanaan. Wajib militer tentunya akan membutuhkan dana yang besar dalam pelaksanaannya sementara itu pendanaan Indonesia masih belum memadai. Hal ini terbukti dalam hal pendanaan untuk prioritas pertahanan negara yang belum terpenuhi, seperti anggaran untuk pertahanan keseluruhan dan alat utama sistem pertahanan (alutsista). Penerapan wajib militer di Indonesia akan mengancam hak konstitusional warga negara dan juga kovenan-kovenan Internasional mengenai Hak Asasi Manusia (HAM). Wajib militer dianggap bertentangan atau berpotensi melanggar beberapa hak, terutama hak untuk hidup (right to life), hak atas kebebasan dan keamanan (right to liberty and security), kebebasan untuk berpikir, hati nurani dan beragama (freedom of thought, conscience and religion). Kata Kunci: Wajib Militer, Kovenan Internasional, Pertahanan Negara